PERBEDAAN SIKAP, PENGETAHUAN DAN ASUPAN GIZI PASIEN KARDIOVASKULER SETELAH DIBERIKAN EDUKASI DENGAN MEDIA VIDEO ANIMASI DAN LEAFLET “CINTAI JANTUNGKU” DI RSUD SITI FATIMAH AZ-ZAHRA PALEMBANG - Rivaldi, Rizky Achlaq; Susyani, Susyani; Podojoyo, Podojoyo (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
If the heart and blood vessels are disturbed, the body will also feel the effects. Cardiovascular disease is a disorder that occurs in the heart and blood vessels, which is quite common in society. Cardiovascular diseases include coronary heart disease, heart failure, hypertension, and stroke. To enhance knowledge and attitudes regarding cardiovascular diseases, one way to do so is through education. It is known that there is a difference in the impact of education using animated video media and leaflets on the knowledge, attitudes, and intake of cardiovascular patients at Siti Fatimah Az-Zahra Regional General Hospital. The type of research used is quantitative research employing a quasi-experimental design with a pretest and posttest arrangement for two groups. The results of this study indicate that there are differences in the average values before and after the intervention in knowledge (p=0.000), attitudes (p=0.000), protein intake (p=0.006), fat intake (p=0.000), and carbohydrate intake (p=0.000). However, there was no significant difference in average energy intake before and after the intervention (p=0.245). It can be concluded that there are differences in knowledge, attitudes, and nutritional intake among cardiovascular patients at Siti Fatimah Az-Zahra Regional Hospital.